Investigation of the mathematical model of the multidimensional automatic control system - Rimas, Jonas (Lietuvos matematikos rinkinys, 2000)
The mathematical model of the mutual synchronisation system composed of n = 2p + 1 (p ∈ N) joined into a ring oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.